Improving Science Literacy through STEMQ-based E-Modules through flipbooks at MA Al-Ihsan Kalijaring Jombang - Al Farros, Ibrahim Yusuf; Prihatiningtyas, Suci; Putra, Ino Angga; Pertiwi, Novia Ayu Sekar; Wulandari, Kartika (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This study aims to analyze the effectiveness of STEMQ-based e-modules in improving students' science literacy at Madrasah Aliyah Al-Ihsan Kalijaring, Jombang. The method used is a pre-experiment with a pretest-posttest design on a single group, involving eleventh-grade students as the sample. Data was collected through a science literacy test that measured students' understanding of optical material before and after using the STEMQ-based e-module. The results showed that the use of the STEMQ-based e-module can improve students' science literacy, particularly in understanding scientific concepts related to optical material. Additionally, the integration of Qur'anic values into the e-module had a positive impact on strengthening students' religious character, supporting holistic learning. The study also found that while most students showed improvement, there was variation in the results, indicating the need for more attention to students with lower science literacy abilities. Overall, the STEMQ-based e-module was proven effective in improving science literacy in the pesantren environment and can serve as a relevant learning medium for 21st-century educational needs. This study contributes to the development of STEM-based learning that integrates religious values in pesantren education.